Concepts and Practice of Humanitarian Medicine - Gunn, S. William A.; Gunn, S. William A.; Masellis, Michele.; Masellis, Michele. (Springer New York : Imprint: Springer, 2008)
Concepts and Practice of Humanitarian Medicine Edited by S. William A. Gunn and Michele Masellis, International Association for Humanitarian Medicine, Switzerland As major events like war, epidemics, and climate change continue to push global health issues to the fore, the international medical community is called upon more than ever to address the needs of the most vulnerable. Concepts and Practice of Humanitarian Medicine brings public health and human rights concerns together, uniting medical, scientific, sociopolitical, and historical perspectives to reaffirm this vision. Forty-one essays from 33 international contributors set out the principles of humanitarian medicine, beginning with the concept of health as a human right, and examining topics such as quality of life, torture, and nuclear conflict. The book draws on important treaties and conventions throughout the history of the United Nations and the World Health Organization, and pays tribute to the efforts of individuals and organizations working to correct health inequities worldwide. A sampling of the topics: The potential of humanitarian medicine in torture prevention and intervention. The varied roles of international and nongovernmental agencies in humanitarian medicine. Critical issues specific to women, children, migrants, refugees, and the poor. Health effects in an increasingly nuclear world. Applications of humanitarian medicine in specialized areas such as heart surgery and trauma. Already acclaimed when first published as the pioneering book, Humanitarian Medicine, this new edition includes 14 additional thought-provoking chapters. The contributors are all major world figures in health and human rights, including Nobel Laureates Kofi Annan and Sir Joseph Rotblat. For those committed to the new health frontiers around the world—particularly researchers, professionals, social scientists, and policymakers in public health, global health, and human rights—Concepts and Practice of Humanitarian Medicine is both informative and empowering reading. Reviews of the first edition: "Challenging… Providing much food for thought. The prestigious authors add to the uniqueness of the publication." –WHO, Health Action in Crises "A galaxy of authors that includes three Nobel Laureates, two Secretaries-General of the United Nations, and two Directors-General of the World Health Organization promises a book of the highest interest. The result fully justifies the promise." –Journal of Humanitarian Medicine "A remarkable array of chapters of prime importance, and a complete view of the technical, philosophical, ethical, and humanist issues to inspire reflection." –Prof. Baron Michel Lechat, Centre de Rechèrches en Epidémiologie des Désastres, Belgium.